Griseofulvin from Xylaria sp. Strain F0010, an Endophytic Fungus of Abies holophylla and its Antifungal Activity Against Plant Pathogenic Fungi - Park, J.H. (Korea Research Institute of Chemical Technology, Daejeon, Republic of Korea); Choi, G.J. (Korea Research Institute of Chemical Technology, Daejeon, Republic of Korea); Lee, H.B. (Seoul National University, Seoul, Republic of Korea); Kim, K.M. (Seoul National University, Seoul, Republic of Korea); Jung, H.S. (Seoul National University, Seoul, Republic of Korea); Lee, S.W. (Korea Research Institute of Chemical Technology, Daejeon, Republic of Korea); Jang, K.S. (Korea Research Institute of Chemical Technology, Daejeon, Republic of Korea); Cho, K.Y. (Korea Research Institute of Chemical Technology, Daejeon, Republic of Korea); Kim, J.C. (Korea Research Institute of Chemical Technology, Daejeon, Republic of Korea), E-mail: kjinc@krict.re.kr (Journal of microbiology and biotechnology, 2005)
Griseofulvin has been used as an antifungal antibiotic for the treatment of mycotic diseases of humans and veterinary animals. The purpose of this work was to identify a griseofulvin-producing endophytic fungus from Abies holophylla and evaluate its in vivo antifungal activity against plant pathogenic fungi. Based on nuclear ribosomal ITS1-5.8SITS2 sequence analysis, the fungus was identified and labeled as Xylaria sp. F0010. Two antifungal substances were purified from liquid cultures of Xylaria sp. F0010, and their chemical identities were determined to be griseofulvin and dechlorogriseofulvin through mass and NMR spectral analyses.